2019
DOI: 10.1182/bloodadvances.2018028720
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacologic control of CAR-T cell function using dasatinib

Abstract: Key Points Dasatinib potently and reversibly suppresses CAR-T cell cytotoxicity, cytokine secretion, and proliferation. Dasatinib could be repurposed as a safety switch to mitigate CAR-mediated toxicity in patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
118
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 175 publications
(123 citation statements)
references
References 27 publications
5
118
0
Order By: Relevance
“…We and others recently demonstrated that dasatinib, an FDA-approved tyrosine kinase inhibitor, suppresses CAR-T cell activation via rapid and reversible antagonism of proximal T cell receptor (TCR) signaling kinases (Mestermann et al, 2019;Weber et al, 2019). Consistent with our previous findings, dasatinib-treated HA.28z CAR-T cells exhibited undetectable phosphorylation of CAR CD3z and ERK1/2 compared to those treated with vehicle ( Figure S6A), indicating that dasatinib potently suppresses tonic signaling in CAR-T cells.…”
Section: Reinvigoration Of Exhausted Car-t Cells Using the Src Kinasesupporting
confidence: 89%
See 2 more Smart Citations
“…We and others recently demonstrated that dasatinib, an FDA-approved tyrosine kinase inhibitor, suppresses CAR-T cell activation via rapid and reversible antagonism of proximal T cell receptor (TCR) signaling kinases (Mestermann et al, 2019;Weber et al, 2019). Consistent with our previous findings, dasatinib-treated HA.28z CAR-T cells exhibited undetectable phosphorylation of CAR CD3z and ERK1/2 compared to those treated with vehicle ( Figure S6A), indicating that dasatinib potently suppresses tonic signaling in CAR-T cells.…”
Section: Reinvigoration Of Exhausted Car-t Cells Using the Src Kinasesupporting
confidence: 89%
“…Similarly, transient rest in a population that had already acquired functional, transcriptional and epigenetic hallmarks of exhaustion, but not aPD-1 blockade, induced impressive functional reinvigoration that was associated with global transcriptional and epigenetic reprogramming. We observed similar phenotypic and functional reinvigoration following transient exposure to dasatinib, a Src kinase inhibitor that potently and reversibly inhibits TCR and CAR signaling (Lee et al, 2010;Mestermann et al, 2019;Schade et al, 2007;Weber et al, 2019). Collectively, these results challenge the paradigm that exhaustion is an epigenetically fixed state (Pauken et al, 2016;Philip et al, 2017) and reveal that transient cessation of CAR signaling may provide a new strategy for augmenting the function of exhausted human CAR-T cell populations.…”
Section: Introductionmentioning
confidence: 61%
See 1 more Smart Citation
“…For example, even in the absence of tonic signaling, how continuous presence of an auto or alloantigen would affect a CAR-or TCRengineered Tregs will be an important consideration. The metabolic phenotype of exhausted Tregs suggests that, as for CD8 + T cells and CD4 + T convs, strategies to modulate signaling pathway activity for example by use of kinase inhibitors (Dufva et al, 2020;Mestermann et al, 2019;Weber et al, 2019;Weber et al, 2020b), or modulation of transcription factor expression Lynn et al, 2019), could be strategies to limit this risk.…”
Section: Ts-car Tregs Are Dysfunctional In Vivo But Not In Vitromentioning
confidence: 99%
“…Drugs identified in this screen as inhibitors of CAR T-cell activity, such as dasatinib, are currently under preclinical evaluation for controlling CAR T cell-mediated toxicities, which will validate the ability of this approach to identify biologically relevant drugs. 9,10 The second mitochondrial-derived activator of caspases (SMAC) mimetic birinapant was identified as enhancing CAR T-cell cytotoxicity against primary B-ALL cells. It may be of interest to evaluate birinapant for potential clinical use in combination with CAR T cells.…”
Section: Tumor Survivalmentioning
confidence: 99%